Impacts of human footprint on habitat quality and permafrost environment in Northeast China - Jianjun Tang; Xiaoying Jin; Haowei Mu; Sizhong Yang; Ruixia He; Xiaoying Li; Wenhui Wang; Shuai Huang; Jiaxing Zu; Hongwei Wang; Zuwang Li; Lin Yang; et al. (Ecological Indicators)
In Northeast China, intensified human footprints have greatly altered ecosystem service functions, leading to biodiversity decline, habitat fragmentation, and permafrost warming and thaw. For regional ecological security, it is crucial to conduct a detailed investigation of how human footprints affect the ecological environment and ground temperatures over the long-term. This study examines spatiotemporal characteristics of human footprints, habitat quality (HQ), and permafrost distribution in Northeast China using human footprint data, the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, and GeoDetector model. The following results were obtained. (1) Between 2000 and 2020, human footprint of Northeast China experienced four growth stages with an overall growth rate of 54.2 %, with the most rapid growth between 2010 and 2015. Built environment and nighttime lights (NTL) significantly contributed to human footprint, while cropland had a relatively low contribution at only 1.3 %. (2) In Northeast China, total HQ decreased by 14.5 %, although high habitat degradation level increased by 2.5 %. The areal extent of high-level HQ patches declined by 12.2 % with rising human footprint index, and the proportion of low- and lower-quality habitats increased significantly. (3) Between 2000 and 2018, mean annual ground temperature in Northeast China increased by 0.15 °C, reflecting significant permafrost degradation and an average annual increase rate of 0.063 °C. During this period, permafrost area decreased by 0.9 × 105 km2, and the southern limit of latitudinal permafrost also shifted northward. (4) Waterways and roads are the main drivers of rising ground temperatures, with waterways having the highest q-value (0.56). The interactions between paired impacting factors also indicate that the highest q-value (0.71) for the intersections of waterways and roads. These research results may contribute to a better understanding of the relationships among human footprint, ecological environment, and ground temperatures in Northeast China, and help provide a basis for ecological conservation.